The influence of time on the dynamics of crime: integrating kozyrev's temporal flows into the homeokinetic approach in criminology - Туляков, Вячеслав Олексійович; Туляков, В. О.; Tuliakov, Viacheslav O. (Elsevier, 2025)
This article examines the integration of Nikolai Kozyrev's theory of time into the homeokinetic approach for analyzing the dynamics of crime as an open system of interaction within the "criminal-victim-environment" triad. It demonstrates that time in this context acts not as a passive backdrop but as an active modulator of flows of matter, energy, and information that shape criminal events. The theoretical foundations, practical cases with statistical trends, and critical limitations of the approach are explored. New directions for research and preventive strategies are proposed, taking into account temporal dynamics. This text was edited with the assistance of AI Grok 5. Translation was created by Perplexity and Grammarly AI'5. All parts of this article, prepared with the involvement of the mentioned AI technologies, have been personally reviewed and edited.
Tuliakov V. The influence of time on the dynamics of crime: integrating kozyrev's temporal flows into the homeokinetic approach in criminology [Online] / Viacheslav Tuliakov // SSRN : website. - Access mode : https://ssrn.com/abstract=5395647 ; http://dx.doi.org/10.2139/ssrn.5395647 ; https://hdl.handle.net/11300/30377 - Publication date : 18.08.2025.
Keywords: homeokinetics; criminology; time; Nikolai Kozyrev; crime; dynamics; spatiotemporal models; social physics; prevention; criminal behavior; кримінологія; час; соціальна фізика; просторово-часові моделі; профілактика